2004
DOI: 10.1016/j.clinph.2003.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Music perception in cochlear implant users: an event-related potential study

Abstract: Objective: Compare the processing of music-syntactic irregularities and physical oddballs between cochlear implant (CI) users and matched controls.Methods: Musical chord sequences were presented, some of which contained functionally irregular chords, or a chord with an instrumental timbre that deviated from the standard timbre.Results: In both controls and CI users, functionally irregular chords elicited early (around 200 ms) and late (around 500 ms) negative electric brain responses (early right anterior nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
59
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 31 publications
11
59
0
Order By: Relevance
“…In a set of studies (Koelsch et al, 2000, 2002, 2003, 2004), a Neapolitan sixth chord was used as the unrelated target. This chord is analyzed in music theory as a substitution of the subdominant chord, which is usually followed by a dominant seventh chord.…”
Section: Simulations Of the Erp Responses To Violations Of Harmonic Rmentioning
confidence: 99%
“…In a set of studies (Koelsch et al, 2000, 2002, 2003, 2004), a Neapolitan sixth chord was used as the unrelated target. This chord is analyzed in music theory as a substitution of the subdominant chord, which is usually followed by a dominant seventh chord.…”
Section: Simulations Of the Erp Responses To Violations Of Harmonic Rmentioning
confidence: 99%
“…In some CI users the absence of artifacts in EEG recordings has been reported (Zhang et al, 2010). Moreover, at least one study suggested electrical artifacts only occur at response latencies different from cortical AEPs and thus did not report difficulties in the measurement of AEPs (Koelsch et al, 2004). It has also been speculated that the CI artifact may be present only until one year after CI activation (Lonka et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have used AEPs to investigate how the auditory cortex adapts to the artificial input provided by a cochlear implant (CI). Examples are the measurement of the P1 response to investigate the functional development of the auditory cortex in children fitted with CIs (Gilley et al, 2008;Sharma et al, 2005), the study of brain asymmetries in the auditory cortex (Debener et al, 2008;Sandmann et al, 2009), the investigation of neural correlates of musical sound perception (Koelsch et al, 2004;Sandmann et al, 2010), and the relationship of AEPs to speech perception (Henkin et al, 2009;Kelly et al, 2005;Lonka et al, 2004;Zhang et al, 2010Zhang et al, , 2011. Based on those and other studies it has been suggested that the functional integrity of the auditory system from CI users, which varies widely across patients, as well as the capacity for cortical plasticity, deserves more attention when investigating implantation outcome (Moore and Shannon, 2009;Wilson and Dorman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, magnetoencephalographic evidence of auditory plasticity has been noted in sudden deafness. 10,11 This plasticity facilitates tone perception in individuals with cochlear implants, which can be mirrored by the progressive optimization of neuromagnetic responses that are evoked by auditory stimuli after implantation.…”
mentioning
confidence: 99%